2007
DOI: 10.1088/1126-6708/2007/05/050
|View full text |Cite
|
Sign up to set email alerts
|

Black saturn

Abstract: Using the inverse scattering method we construct an exact stationary asymptotically flat 4+1-dimensional vacuum solution describing "black saturn": a spherical black hole surrounded by a black ring. Angular momentum keeps the configuration in equilibrium. Black saturn reveals a number of interesting gravitational phenomena: (1) The balanced solution exhibits 2-fold continuous non-uniqueness for fixed mass and angular momentum;(2) Remarkably, the 4+1d Schwarzschild black hole is not unique, since the black ring… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
528
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(538 citation statements)
references
References 54 publications
9
528
1
Order By: Relevance
“…For example, with a proper choice of the function V (ρ) this allows to describe the bending of a black string in the background of static black holes and thus construct thin black Saturns, in the sense that the black ring surrounding the black hole is thin. Exact solutions for black Saturns in five-dimensional vacuum gravity were obtained in [31]. Our approach here allows to extend them and could be used to refine the arguments in [32].…”
Section: Black Saturnsmentioning
confidence: 96%
“…For example, with a proper choice of the function V (ρ) this allows to describe the bending of a black string in the background of static black holes and thus construct thin black Saturns, in the sense that the black ring surrounding the black hole is thin. Exact solutions for black Saturns in five-dimensional vacuum gravity were obtained in [31]. Our approach here allows to extend them and could be used to refine the arguments in [32].…”
Section: Black Saturnsmentioning
confidence: 96%
“…In fact, it has been used with much success to generate new black-hole solutions in five dimensions, such as the doubly rotating black ring [5,7], multiple-horizon solutions like the black Saturn [25] and bi-ring [26], as well as black holes on non-trivial gravitational instanton backgrounds [8]. A recent review of some of this progress can be found in [17].…”
Section: Ism Constructionmentioning
confidence: 99%
“…In particular, a multi-black hole configuration with k black holes has k independent parameters. This implies a continuous non-uniqueness in the (µ, n) phase diagram (or for a given mass), much like the one observed for bubble-black hole sequences [49] and for other classes of black hole solutions [99,17,19,18] (see also Sec. 6).…”
Section: Consequences For the Phase Diagrammentioning
confidence: 61%
“…The qualitative behavior of the non-uniform string branch depends on the sign of γ. If γ is positive, then the branch emerges at the mass µ = µ GL with increasing µ and decreasing n. If instead γ is negative the branch emerges at µ = µ GL with decreasing µ and decreasing n. To see what this means for the entropy we note that from (17) and the first law of thermodynamics one finds…”
Section: Non-uniform Black Stringmentioning
confidence: 97%
See 1 more Smart Citation